2019
DOI: 10.1007/s10534-019-00224-1
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and solution chemistry, antiproliferative effects, and serum albumin binding of three pseudohalide derivatives of auranofin

Abstract: Three pseudohalide analogues of the established gold drug Auranofin (AF hereafter), of general formula Au(PEt 3 )X, i.e. Au(PEt 3 )CN, Au(PEt 3 )SCN and Au(PEt 3 )N 3 (respectively denoted as AFCN, AFSCN and AFN 3 ), were prepared and characterized. The crystal structure was solved for Au(PEt 3 )SCN highlighting the classical linear geometry of the 2-coordinate gold(I) center. The solution behaviour of the compounds was then comparatively analysed through 31 PNMR providing evidence for an acceptable stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…This prompted investigators to analyze in detail the reactions of medicinal gold compounds with proteins. A systematic investigation on the interactions of the reference gold(I) drug auranofin with a series of model proteins, i.e., human serum albumin, carbonic anhydrase, superoxide dismutase, and hemoglobin, was recently carried out in our laboratory through mass spectrometry, and the resulting adducts could be characterized in molecular detail (Pratesi et al, 2016(Pratesi et al, , 2018(Pratesi et al, , 2019Magherini et al, 2018;Cirri et al, 2019;Zoppi et al, 2020). These studies revealed that auranofin targets quite selectively the free cysteine residues of proteins (Pratesi et al, 2018;Zoppi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This prompted investigators to analyze in detail the reactions of medicinal gold compounds with proteins. A systematic investigation on the interactions of the reference gold(I) drug auranofin with a series of model proteins, i.e., human serum albumin, carbonic anhydrase, superoxide dismutase, and hemoglobin, was recently carried out in our laboratory through mass spectrometry, and the resulting adducts could be characterized in molecular detail (Pratesi et al, 2016(Pratesi et al, , 2018(Pratesi et al, , 2019Magherini et al, 2018;Cirri et al, 2019;Zoppi et al, 2020). These studies revealed that auranofin targets quite selectively the free cysteine residues of proteins (Pratesi et al, 2018;Zoppi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Starting from our previous findings on the reactivity of AF and its analogs toward protein targets (Pratesi et al, 2014(Pratesi et al, , 2018Marzo et al, 2017Marzo et al, , 2019Cirri et al, 2019;Zoppi et al, 2020), here we have extended the investigation-at the molecular levelon the mode of action of these medicinally relevant gold(I) compounds. Specifically, we have focused our attention on AF and its analog where the thiosugar moiety is replaced by the iodide ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the biologically active [Au(PEt 3 )] + moiety is not affected by this modification. A systematic and comparative investigation concerning the effects on the anticancer properties of the structural modifications was also performed (Cirri et al, 2017(Cirri et al, , 2019Marzo et al, 2017Marzo et al, , 2019. Through this approach, the complex Au(PEt 3 )I, i.e., the analog of AF where the thiosugar moiety is replaced by iodide, was eventually selected thanks to the very favorable biochemical profile accompanied by a remarkable anticancer activity (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Then, the antiproliferative properties of two of these analogs, i.e., Et 3 PAuCl and Et 3 PAuI, as well as auranofin itself were comparatively assayed in vitro against four representative colorectal cancer lines, i.e., HCT8, HCT116, HT29, and Caco2, and two healthy cell lines, i.e., HDF (human fibroblast, adult) and HEK293 (human embryonic kidney), by using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) test [51] . As displayed in Table 1, all tested compounds produced very notable cytotoxic effects on all the selected CRC cell lines with half-maximal inhibitory concentration (IC 50 ) values always falling in the 100-700 nM range.…”
Section: Auranofin and Its Analogs Show Promise For Colorectal Cancer Treatment: In Vitro Evidencementioning
confidence: 99%
“…Moreover, the present results confirm that Et 3 PAuCl is not only the most potent cytotoxic agent but also the most potent TrxR inhibitor of the series; although the IC 50 values measured for auranofin and Et 3 PAuI are only slightly higher, they still The results are reported as the average value for three independent experiments ± standard deviation. Reproduced and adapted with permission from Marzo et al [51] . IC 50 : Half-maximal inhibitory concentration; AF: auranofin.…”
Section: Auranofin and Its Analogs Show Promise For Colorectal Cancer Treatment: In Vitro Evidencementioning
confidence: 99%